Nanofluidic Power: Anomalous pH‐Dependent Nanofluidic Salinity Gradient Power (Small 48/2017). Issue 48 (19th December 2017) - Yeh, Li‐Hsien; Chen, Fu; Chiou, Yu‐Ting; Su, Yen‐Shao
Abstract : Li‐Hsien Yeh and co‐workers, report for the first time, in article number1702691, that a nanopore having smaller surface charge density can export remarkably higher nanofluidic salinity gradient power (NSGP). The counterintuitive, surface‐charge‐dependent NSGP behavior is demonstrated, caused by the pH‐dependent ion concentration polarization effect, which results in the reduction of the effective concentration ratio across a nanopore.